Ecological risk assessment of mercury to soil fauna in tropical forest, Southeastern, Brazil - Buch, Andressa Cristhy (2017)
Atmospheric pollution by mercury (Hg) is of great concern to all humanity, as its physicochemical characteristics confer this toxic metal ability to travel long distances around the planet. Currently has been observed mainly in industrialized countries, the increasing levels of Hg in the atmosphere arising from anthropogenic sources. Brazil is the seventh country with the highest rate of mercury in the atmosphere. The major input of Hg to ecosystems is through atmospheric deposition (wet and dry), being transported in the atmosphere over large distances. Forest biomes are of great importance in the atmosphere/soil cycling of elemental Hg through foliar uptake and subsequent transfer of this to the soil through litter, playing an important role as sink of this element. The Atlantic Forest of Brazil is a major storehouse of fauna and flora biodiversity, and according to recent studies this biome has high concentrations of mercury in litter, similar to those found in Chinese in Subtropical Forest. Ecotoxicological assessments can predict the potential ecological risk that the toxicity of Hg in the soil can lead to soil fauna and indirectly impact other trophic levels of the food chain within one or more ecosystems. This thesis aimed to determine mercury levels that represent risks to diversity and functioning of soil fauna in tropical forest soils, as a key tool in Ecological Risk Assessment (ERA). Two Forest Conservation Units of the State of Rio de Janeiro were selected for the study. The first is a city Park, located next to chlor-alkalis industries and to an important petroleum refinery in activity since 1961, whereas the second is a national Park located next to a refinery under construction, which will be the largest refinery of Brazil, beginning in 2017. This site represents a forest with lower anthropogenic impacts. In these Units were carried out whole chemistry, environmental and ecological characterisations. Results indicated higher mercury concentrations in litter and soil from the forest close to industrial activities. The presence of Hg in this soil influenced the abundance and diversity of taxonomic groups of soil fauna. Soil properties such as organic matter and pH did interact with the mercury and the organisms, showing the importance of the soil type in ERA. In toxicity tests the reproduction was the endpoint more sensitive for meso and macrofauna in soils spiked with Hg+2. Earthworms showed greater accumulation of mercury in their tissues than in casts. Among the climatic fators evaluated in the laboratory, the increase of temperature (from 20˚ to 24 ˚C) did not influence Hg toxicity to Collembola. However extreme soil moisture conditions increased Hg toxicity to enchytraeids. The lowest observed effect concentration was of 1 mg Hg kg-1 to Collembola, indicating a need for a greater restriction in the levels of mercury load in soil recommended by the CONAMA. Since mercury biomagnification and methylation processes can occur along the food chain.